Direct Democracy in Europe Developments and Prospects - Pállinger, Zoltán Tibor; Kaufmann, Bruno; Marxer, Wilfried; Schiller, Theo.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften : Imprint: VS Verlag für Sozialwissenschaften, 2007)
Modern direct democracy has recently become an essential element of political life in many countries in Europe - and worldwide. The initiative and referendum process offers extra channels of participation and can serve as an important supplementary institution in representative democratic systems. This first volume of the new series Direct Democracy in Modern Europe features sixteen systematic and broadly empirical approaches to the study of modern direct democracy within the context of European politics including - system contexts and effects of the initiative and referendum process - theoretical approaches and basic values in modern direct democracy - the quality and institutional design of direct democratic mechanisms - aspects of information and communication - institutional performance and economic effectiveness - transnational challenges and the development of direct democracy in Europe.
System contexts and system effects of direct democracy - direct democracy in Liechtenstein and Switzerland compared -- Direct-democratic procedures as corrective mechanisms in consociational systems or for clientelistic structures—some brief remarks -- A Double Integration Policy Divide: Votes and Interest Group Recommendations in Switzerland -- Direct Democracy and Theories of Participatory Democracy—some observations -- The design determines the quality — some criteria for determining the design and the quality of direct democracy -- Reflections on the social production of incompetent citizens -- The role of the political elite in Swiss direct-democratic votes -- Beyond Information and Opinion. The importance of public communication in the referendum process -- On the economic efficiency of direct democracy -- Direct Democracy and Citizens’ Information about Politics -- Prospects for Transnational Direct Democracy—Exploring the New European Approach to Citizens’ Power beyond the Nation-State -- Voting Behaviour in the European Constitution Process -- Referendums and Ratification of the EU Constitution -- Referendum experience in Slovakia: a long and winding road -- Prospects for Participatory Democracy in the Supranational Constitutionalism of the European Union -- Databases for (empirical) research on “direct democracy”.
Keywords: Political science; Comparative politics; Political Science; Comparative Politics